2016
DOI: 10.1523/jneurosci.4032-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in Postencoding Connectivity with High-Level Visual Cortex Is Associated with Reward-Motivated Memory

Abstract: Reward motivation has been demonstrated to enhance declarative memory by facilitating systems-level consolidation. Although highreward information is often intermixed with lower reward information during an experience, memory for high value information is prioritized. How is this selectivity achieved? One possibility is that postencoding consolidation processes bias memory strengthening to those representations associated with higher reward. To test this hypothesis, we investigated the influence of differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
141
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 43 publications
14
141
2
1
Order By: Relevance
“…Relevant to the discussion here, recent work suggests that postencoding hippocampal activity and functional connectivity immediately following an event may enhance associative memory of that just‐experienced information (Murty et al, ; Tambini & Davachi, ; Tambini et al, ). These neural patterns even emerge if measured in the few seconds following an item's presentation (Cohen et al, ; Staresina et al,).…”
Section: Retroactive Mechanisms Of Binding Sequential Memory Represenmentioning
confidence: 64%
See 1 more Smart Citation
“…Relevant to the discussion here, recent work suggests that postencoding hippocampal activity and functional connectivity immediately following an event may enhance associative memory of that just‐experienced information (Murty et al, ; Tambini & Davachi, ; Tambini et al, ). These neural patterns even emerge if measured in the few seconds following an item's presentation (Cohen et al, ; Staresina et al,).…”
Section: Retroactive Mechanisms Of Binding Sequential Memory Represenmentioning
confidence: 64%
“…Such rapid neural replay has been hypothesized to be important for preserving memory for the sequential order of recent information, although more evidence supporting this hypothesis is needed (Ólafsdóttir, Bush, & Barry, ). Identifying similar postencoding replay and/or reactivation patterns in humans is an intense and active area of research (de Voogd, Fernández, & Hermans, ; Gruber, Ritchey, Wang, Doss, & Ranganath, ; Murty, Tompary, Adcock, & Davachi, ; Schlichting & Preston, , ; Tambini, Ketz, & Davachi, ; Tambini, Rimmele, Phelps, & Davachi, ; Tompary, Duncan, & Davachi, ).…”
Section: Retroactive Mechanisms Of Binding Sequential Memory Represenmentioning
confidence: 99%
“…Further, emotional learning, albeit in the aversive domain, has been shown to restructure representations of objects in category-selective cortex (i.e., animal versus tool cortex) associated with reinforcement (Dunsmoor et al 2014). Finally, reward motivation, albeit in an intentional encoding paradigm, has been shown to selectively facilitate post-encoding interactions of the ventral tegmental area, the source of dopamine neurons, and the hippocampus with category-selective cortex in service of better memory (Murty et al 2016b). Future work, however, will have to validate this proposed mechanism of retroactive memory enhancements by reward.…”
mentioning
confidence: 99%
“…One area of research in which the motivation to participate and thus the method of participant compensation might be critical to the results of the study is in experiments examining the effects of motivation on task performance. In the design adopted by many studies examining motivation (e.g., Adcock, Thangavel, Whitfield-Gabrieli, Knutson, & Gabrieli, 2006;Murayama & Kitagami, 2014;Murty, Tompary, Adcock, & Davachi, 2016;Shigemune et al, 2010;Spaniol, Bowen, Wegier, & Grady, 2015;Spaniol, Schain, & Bowen, 2013;Wittmann et al, 2005), in addition to compensation for time, rewards are manipulated within task and used as incentive for participants to earn additional monetary rewards based on their task performance. In these studies, the overall finding is that memory for items associated with a high reward are remembered better than items associated with a low reward.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the overjustification effect, those who choose to be compensated with for their time with credit, may be more intrinsically motivated to participate thus extra performance based incentives may interfere with their willingness or ability to perform the task well. We chose to examine this within the context of a rewarded memory task where better memory for high versus low reward (e.g., Adcock et al, 2006;Murty, LaBar, Hamilton, & Adcock, 2011;Murty et al, 2016) usually only after a period of consolidation (e.g., Murayama & Kitagami, 2014;Murayama & Kuhbandner, 2011;Spaniol et al, 2013) is a robust finding, but the motivation and compensation for completing the study is rarely reported nor included as a factor in the results.…”
Section: Introductionmentioning
confidence: 99%